Can optimism mediate the negative effect of trait anxiety on psychological well-being? - Gutiérrez-Carmona, Andrés; Alday Mondaca, Carolina; Urzúa, Alfonso; Wlodarczyk, Anna (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
The objective of the study was to evaluate the mediating effect of optimism in the anxiety-trait relationship and psychological well-being in higher education students. The sample consisted of 332 students of higher education in Antofagasta, Chile, with an average age of 21.8 years. It is found that the negative effect of anxiety-trait on the dimensions of psychological well-being diminishes when incorporating optimism in the regression. It is concluded that optimism has a partial mediating effect on the dimensions of psychological well-being, except in personal growth, where it exercises total mediation.